FORMULASI SEDIAAN CREAM BLUSH ON MENGGUNAKAN EKSTRAK BUNGA MAWAR MERAH (Rosa damascena P.Mill) SEBAGAI PEWARNA ALAMI - Tampubolon, Antetti (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
Blush on is a form of cosmetic preparation, aiming to give color to the cheeks and dimensions to the face. The purpose of this study was to determine the possibility of red rose extract (Rosa damascena P. Mill.) to be formulated as a blush on cream preparation, and the effective concentration to fulfill physical tests and evaluations. This research is an experimental study. Data collection was carried out through the formulation of blush on cream with the addition of red rose flower extract in a concentration combination of 10%, 20% and 30%. Then organoleptic test, stability test, pH test, topical test, irritation test, and hedonic test were carried out. Through research it is known that the preparation of blush on cream from red rose flower extract: fulfills the physical evaluation test and stability test; while the hedonic test at concentrations of 0% and 10% were included in the preferred category, and preparations at concentrations of 20% and 30% were included in the very preferred category by the panelists. The conclusion of this study is that cream blush from red rose flower extract is able to produce preparations that meet physical tests and evaluations; and can be formulated as a natural dye in blush on cream preparations that produce pale pink, intense pink, and intense red colors. The higher the concentration of the extract, the darker the resulting color.